Correlation between NAD(P)H: quinone oxidoreductase 1 C609T polymorphism and increased risk of esophageal cancer: evidence from a meta-analysis. (January 2017) - Diao, Jingfang; Bao, Jie; Peng, Jianxin; Mo, Jiaqiang; Ye, Qing; He, Junming
NAD(P)H: quinone oxidoreductase 1 (NQO1) C609T gene polymorphisms have been reported to influence the risk for esophageal cancer (EC) in many studies. However, the results remain controversial and ambiguous. We performed a meta-analysis, which included 13 independent studies with a total of 2357 subjects, to examine the association between NQO1 C609T polymorphism and EC. The association was assessed by five different gene models. The overall analysis suggested that the variant allele and genotypes were significantly related to increased risk of EC (odds ratio [OR] T versus C = 1.15, 95% confidence interval [CI] 0.95–1.40, probability of rejection [POR] = 0.014; OR TT versus CC = 1.32, 95% CI 1.01–1.73, POR = 0.045; OR TC versus CC = 1.32, 95% CI 0.98–1.21, POR = 0.128; OR TT + TC versus CC = 1.10, 95% CI 1.00–1.20, POR = 0.05; OR TT versus CC + TC = 1.26, 95% CI 0.95–1.57, POR = 0.103). Sensitivity analysis confirmed the reliability of these findings. Our study shows that individuals carrying the NQO1 C609T variant allele and genotypes are more susceptible to EC.